Corporate boards: why their most important duty is the hardest to achieve - George, Bill (Henry Stewart Talks, 2025)
Leading in chaotic times, Board engagement, Internal leadership development, Board culture, Understanding the role of the CEO, Board governance, Transparency vs. politicking